Synthesis, Spectroscopic Characterization and Thermal Study of Some Transition Metal Complexes of 2-Amino-N’-[(1E,2Z)-2-(hydroxyimino)-1-phenylethylidene]-4,5,6,7-tetrahydro-1-benzothiophene-3-carbohydrazide - Z. Bootwala, Sakina (Asian Journal of Chemistry, 2012)
Complexes of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) with an asymmetric tridentate hydrazones derivative synthesized from 2-amino-4,5,6,7-tetrahydro-1-benzothiophene-3-carbohydrazide and (2E)-2-(hydroxyimino)-1-phenylethanone were synthesized and characterized by analytical analysis and physical-chemical methods. The IR spectral data suggested that the ligand behaves as a monobasic tridentate ligand towards the central metal ion with an ONO donor atom sequentially. From the micro analytical data, the stiochiometry of the complexes 1:1 (metal: ligand) of Cu(II) and Zn(II) complexes, where as 1:2 (metal:ligand) of Mn(II),Co(II) and Ni(II) complexes. The physico-chemical data suggested distorted square planer geometry of Cu(II) complex, tetrahedral geometry of Zn(II) complex and octahedral geometry for the Mn(II), Co(II) and Ni(II) complexes. The thermal behaviour (TGA/DTA) of the complexes were studied and kinetic parameter were determined by Coats-Redfern method.